1996
DOI: 10.3109/00016359609003520
|View full text |Cite
|
Sign up to set email alerts
|

Defensive characteristics in individuals with amalgam illness as measured by the percept-genetic method Defense Mechanism Test

Abstract: Twenty patients complaining of symptoms deriving from their amalgam fillings and a non-patient group were assessed by means of the perceptual projective Defense Mechanism Test (DMT). The test protocols were scored for 130 DMT variables and analyzed by means of the multivariate statistical method Partial Least Squares discriminant analysis. The objective was to try to distinguish the group with amalgam illness from the non-patient group by means of the DMT. The results showed that it was possible to distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…68 The results were compared to those of 37 controls. The authors reported that the amalgam illness group exhibited more inappropriate reactions to threats and used denial as a primary coping mechanism.…”
Section: Amalgam Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…68 The results were compared to those of 37 controls. The authors reported that the amalgam illness group exhibited more inappropriate reactions to threats and used denial as a primary coping mechanism.…”
Section: Amalgam Illnessmentioning
confidence: 99%
“…[65][66] The results from a number of studies suggest that psychological illness and not mercury from amalgam restorations is an important element in amalgam illness. [67][68][69][70][71] One study involved 218 patients with selfreported oral galvanism; no findings suggestive of either acute or chronic mercury intoxication were found. 72 Of these patients, 43% were diagnosed with a psychological disorder, often anxiety or panic disorders.…”
Section: Amalgam Illnessmentioning
confidence: 99%
“…The available coping strategies of patients with amalgam-related complaints seem to be inadequately adaptive to handle threatening situations compared to the coping styles of a control group without complaints [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Ahlgren et al (2002),Ahlqwist et al (1999),Alanko et al (1996),Apostoli et al (2002),Archbold et al (2004),Athavale et al (2003),Attin et al (1998),Aw et al (2005),Bagedahl-Strindlund et al (1997),Bailer et al (2001),Bangsi et al (1998), Bellinger et al (2006,Bergdahl et al (1998),Berglund & Molin (1996),Biocina-Lukenda et al (2004),Blomgren et al (1996),Bratel et al (1996Bratel et al ( , 1997,Browning et al (1997), Casetta et al (2001), Chong & Pitt (2005), Dalen et al (2003a, 2003b), DeRouen et al (2006), Dohrn & Neuser (2001), Dunne & Abraham (2000), Dunsche et al (2003), Eden et al (2002), Faccioni et al (2003), Factor-Litvak et al (2003), Fernandes et al (1998), Ganss et al (2000),Gottwald et al (2001),Grandjean et al (1997),Hayashi & Wilson (2003),Henningsson & Sundbom (1996),Herrstrom et al (1996Herrstrom et al ( , 1997,Hol et al (2001),Ibbotson et al (1996),Issa et al (2005),Jacobsen & Hensten-Pettersen (2003),Janson et al (1998),Khamaysi et al (2006),Koch (1999),Kosugi et al (2003),Laeijendecker et al (2004),Laine et al (1997aLaine et al ( , 1997bLaine et al ( , 1999,Langworth et al (2002),…”
mentioning
confidence: 99%